2010
DOI: 10.1182/blood-2009-09-220020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the translational machinery as a novel treatment strategy for hematologic malignancies

Abstract: IntroductionEukaryotic cells have various mechanisms and levels by which gene expression can be regulated including: transcription, export of mRNA messages, mRNA stability, and posttranslational modifications. Protein synthesis is essential for cell viability, and controlling mRNA translation is a critical step in regulation of gene expression. Translation can be divided between 3 stages: initiation, elongation, and termination. Translational control is principally exerted by regulating the formation of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 115 publications
(120 reference statements)
2
76
0
Order By: Relevance
“…2C). We observed that addition of CD2 costimulation produced a reproducible increase in S6-Rp phosphorylation in all of the subsets, irrespective of basal status, supporting a role for CD2-induced signals in the regulation of translation at the level of S6-Rp (37). Although the CD2-regulated S6-Rp phosphorylation was in agreement with the kinetics of Akt activation in naive T cells, albeit with a different amplitude consistent with downstream amplification at the S6-Rp level, this did not appear to be the case in effector/memory subsets, indicating the influence of other components of a CD2-regulated signal network in effector/memory T cells (Fig.…”
Section: The Journal Of Immunology 5235mentioning
confidence: 68%
“…2C). We observed that addition of CD2 costimulation produced a reproducible increase in S6-Rp phosphorylation in all of the subsets, irrespective of basal status, supporting a role for CD2-induced signals in the regulation of translation at the level of S6-Rp (37). Although the CD2-regulated S6-Rp phosphorylation was in agreement with the kinetics of Akt activation in naive T cells, albeit with a different amplitude consistent with downstream amplification at the S6-Rp level, this did not appear to be the case in effector/memory subsets, indicating the influence of other components of a CD2-regulated signal network in effector/memory T cells (Fig.…”
Section: The Journal Of Immunology 5235mentioning
confidence: 68%
“…Translation of mRNA is tightly regulated at the initiation level through the assembly of eIF4F complexes. 27 Using Jurkat cells, we compared the effects of rapamycin, PP-242 and OSI-027 on eIF4F assembly by pull-down assays using 7 methyl-GTP-Sepharose beads that mimic the cap structure of mRNA. 28 Although exposure to rapamycin did not change the amount of eIF4G or 4E-BP1 bound to eIF4E, incubation with either PP-242 or OSI-027 increased the Active site mTOR inhibitors in T-ALL C Evangelisti et al 4E-BP1 levels and decreased the amounts of eIF4G bound to eIF4E, indicating a major inhibition of eIF4F complex assembly (Figure 3c).…”
Section: Effects Of Active Site Mtor Inhibitors On Mrna Translationmentioning
confidence: 99%
“…Translation of mRNA is tightly regulated at the initiation level through the assembly of eIF4F complexes. 30 Using Jurkat cells, we compared the effects of rapamycin and metformin on eIF4F assembly by pull-down assays using 7methyl-GTP-Sepharose beads that mimic the cap structure of mRNA. 20 While exposure to metformin dissociated eIF4G from eIF4E and increased the amount of 4E-BP1 bound to eIF4E, indicating inhibition of eIF4F complex assembly, treatment with rapamycin did not change the amount of eIF4G or 4E-BP1 bound to eIF4E (Figure 4c).…”
Section: Metformin Inhibits Mrna Translation In T-all Cellsmentioning
confidence: 99%